(untitled) (Economics and region, 2021)
The article actualizes the issue of ensuring information security of Ukraine in the conditions of deepening digital transformations of the national economy. The necessity of forming a favorable regulatory environment as a basis for developing effective forms of implementing state policy in the field of information security is substantiated. The theoretical and methodological basis for the study of institutional support for information security identified the fundamental provisions of institutionalism and neo-institutionalism. The article details and systematizes the categorical apparatus of institutionalism. The author’s definition of institutional support of information security is presented and institutional-legal and institutional-organizational support is singled out in its structure. Based on the use of a systematic approach, the architecture of institutional support of information security is presented.